The Effect of Perception of Ease of Use and Quality of Service on the Willingness to Adopt myBCA Mobile Banking with Trust as a Mediating Variable - Denia Azizah Purbantoro; Widayat Widayat (Jurnal Manajemen Bisnis dan Kewirausahaan, 2026)
This study aims to examine the effect of Perceived Ease of Use and Service Quality on the Willingness to Use the myBCA mobile banking application of Bank Central Asia, with Trust as a mediating variable. A quantitative survey design was employed involving 384 active myBCA users in Malang, Indonesia (n = 384), selected through accidental sampling. Data were analyzed using multiple linear regression and path analysis with SPSS 29. The key variables analyzed include Perceived Ease of Use, Service Quality, Trust, and Willingness to Use Technology. The results indicate that Perceived Ease of Use (β = 0.338; t = 7.008; p < 0.001) and Service Quality (β = 0.385; t = 7.981; p < 0.001) have positive and significant effects on Willingness to Use. Both Perceived Ease of Use (β = 0.245; p < 0.001) and Service Quality (β = 0.241; p < 0.001) significantly influence Trust, which in turn significantly affects Willingness to Use (β = 0.233; p < 0.001). The indirect effects through Trust (0.057 and 0.056) are smaller than the direct effects, indicating partial mediation, confirmed by Sobel test values of 3.888 and 4.189 (p < 0.05). The model explains a substantial proportion of variance in user willingness (R² = 0.259). Theoretically, this study extends the Technology Acceptance Model by integrating service quality and trust within a contemporary digital banking context. Practically, the findings highlight the strategic importance of enhancing system usability and service excellence to strengthen user trust and increase technology adoption. These results imply that trust-building mechanisms are pivotal in accelerating sustainable digital banking adoption in Indonesia. Overall, the study underscores that ease of use and service quality, reinforced by trust, form a critical foundation for advancing mobile banking utilization.